Human Umbilical Cord Mesenchymal Stem Cells Improve Locomotor Function in Parkinson’s Disease Mouse Model Through Regulating Intestinal Microorganisms - Sun, Zhengqin; Gu, Ping; Xu, Hongjun; Zhao, Wei; Zhou, Yongjie; Zhou, Luyang; Zhang, Zhongxia; Wang, Wenting; Han, Rui; Chai, Xiqing; An, Shengjun (Frontiers in Cell and Developmental Biology, 2022)
Parkinson's disease (PD) is a progressive neurological disorder characterized by a loss of neurons synthesizing dopamine, and subsequent impaired movement. Umbilical cord mesenchymal stem cells (UC-MSCs) exert neuroprotection effects in a rodent model of PD. However, the mechanism underlying UC-MSCs generated neuroprotection is not fully elucidated. In the present study, we found that intranasal administration of UC-MSCs significantly alleviated locomotor deficits and rescued dopaminergic neurons through inhibiting neuroinflammation in an MPTP injury animal model. Furthermore, UC-MSCs treatment altered gut microbiota composition characterized by decreased phylum Proteobacteria, class Gammaproteobacteria, family Enterobacteriaceae, and genus Escherichia Shigella. In addition, the neurotransmitter dopamine in the striatum and 5-hydroxytryptamine in the colon were also modulated by UC-MSCs. Meanwhile, UC-MSCs significantly maintained intestinal goblet cells, which secret mucus as a mechanical barrier against pathogens. Further, UC-MSCs alleviate the higher level of TNF-α and IL-6 as well as the conversion of NF-κB expression in the colon, indicating that inflammatory responses were blocked by UC-MSCs. PICRUSt showed that some pathways including bacterial invasion of epithelial cells, fluorobenzoate degradation, and pathogenic Escherichia coli infection were significantly reversed by UC-MSCs. These data suggest that the beneficial effects were detected following UC-MSCs intranasal transplantation in MPTP-treated mice. There is a possible neuroprotective role of UC-MSCs in MPTP-induced PD mice by crosstalk between brain and gut.